Using DGPS to locate a lawnmower robot - Castro, Diogo Sousa (2021)
There are GNSS sensors that can achieve an accuracy to the centimeter, RTK-GPS, however they are very expensive systems, with limited stock and dominated by only one supplier, with limited support. This master’s thesis aims to study and test the accuracy of a differential GPS system to be applied to the Indego, a lawnmower robot. The system was proposed by (Svatoñ, 2016) using low-cost GNSS receivers, ideal for implementation in lawn mowing robots without significantly increasing their cost. The system contains two distinct parts, the base and the mobile. The base has a fixed location and evaluates the differences between its position and the measured position. The mobile part is intended to be applied to Indego and as such its location is variable. The system is composed of 2 equal GPS receivers, 2 microcontrollers that communicate wirelessly, 2 different antennas, the base has the antenna with higher gain and higher bandwidth. To evaluate the accuracy of the system 3 different tests were performed, the first being a test with the fixed system to evaluate the performance of the receivers. In the second test the mobile part of the system was placed in an Indego and a special square-shaped cutting mode was activated. The last one consists of a trapezoid traversed by the mobile part to evaluate the performance of the system in more distant positions. The results obtained are similar to those published by (Svatoñ, 2016) and by (Kim, 2013).